The matricellular protein CCN5 induces apoptosis in myofibroblasts through SMAD7-mediated inhibition of NFκB. - Mai Tuyet Nguyen; Min-Ah Lee; Young-Kook Kim; Hyun Kook; Dongtak Jeong; Seung Pil Jang; Tae Hwan Kwak; Woo Jin Park (PLoS ONE, 2022)
We previously showed that the matricellular protein CCN5 reverses established cardiac fibrosis (CF) through inducing apoptosis in myofibroblasts (MyoFBs) but not in cardiomyocytes or fibroblasts (FBs). In this study, we set out to elucidate the molecular mechanisms underlying CCN5-mediated selective apoptosis of MyoFBs. We first observed that the apoptotic protein p53 and the anti-apoptotic protein NFκB are simultaneously induced in MyoFBs. When the expression level of p53 was suppressed using a siRNA, CCN5 did not induce apoptosis in MyoFBs. By contrast, when NFκB signaling was inhibited using IKK VII, an IκB inhibitor, MyoFBs underwent apoptosis even in the absence of CCN5. SMAD7 is one of the downstream targets of CCN5 and it was previously shown to potentiate apoptosis in epithelial cells through inhibition of NFκB. In accordance with these reports, when the expression of SMAD7 was suppressed using a siRNA, NFκB signaling was enhanced, and CCN5 did not induce apoptosis. Lastly, we used a luciferase reporter construct to show that CCN5 positively regulated SMAD7 expression at the transcriptional level. Collectively, our data suggest that a delicate balance between the two mutually antagonistic proteins p53 and NFκB is maintained for MyoFBs to survive, and CCN5 tips the balance in favor of the apoptotic protein p53. This study provides insight into the anti-fibrotic activity of CCN5 during the regression of CF.